Analisis dan Perancangan Sistem Informasi Pengelolaan Skripsi dan Praktek Kerja Lapangan - Widyasari Puspa Permata Witra; Mochamad Chandra Saputra; Bayu Priyambadha (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
University of Muhammadiyah Gresik (UMG) is private university that has many faculties and study program, one of them is Industrial Engineering (TI). TI UMG has a web-based information system called Academic Information System (SIAKAD). SIAKAD is a system at the university level that only serves for filling card study plan (KRS) and lecturers marking grades only, not including on the management of submission of Job Training (PKL), Thesis, Seminar and Thesis Defence. Some activities in TI UMG are done by manual procedure such as: job training and thesis registration. Three out of seven respondents say that without the system, number of students that have registered and have not is unknown. Two of the seven respondents stated that the current system is still less efficient. Therefore, a system is needed to fix the existing problem. The purpose of this research is to design a Thesis dan Field Job Practice Management Information System using Ripple methodology with design testing using Requirement Traceability. The results of this study are class diagrams, sequence diagrams, database schema and interface design. Then the results of the design tests show each requirement has unique code that can be traced to features, use cases, communication and sequence diagrams.